The role of serial point-of-care ultrasound during cardiac arrest to predict termination of resuscitation - Farhad Heydari; Mehdi Nasr Isfahani; Babak Masoumi; Sayed Hamed Khajebashi; Forough Hajian; Fatemeh Soleimani (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background The decision to terminate cardiopulmonary resuscitation (CPR) remains challenging, particularly for patients with non-shockable rhythms (asystole/pulseless electrical activity). This study evaluated the role of serial point-of-care ultrasound (POCUS) in predicting the termination of resuscitation by analyzing cardiac standstill duration. Methods A prospective cohort study was conducted from June 2024 to March 2025 in two academic hospitals. Adult patients (n = 154) with non-traumatic cardiac arrest (out-of-hospital or in-hospital) and non-shockable rhythms were included. Serial POCUS was performed every 2 min during CPR to assess cardiac activity. Demographics, arrest characteristics, and outcomes (death, return of spontaneous circulation [ROSC], survival to discharge) were recorded. Statistical analyses included ROC curves to determine predictive values of cardiac standstill duration for non-ROSC. Results The mean age of patients was 65.19 ± 11.63 years old (a range of 35–92) and 117 (76.0%) patients were male. ROSC occurred in 24.7% of cases, and 5.8% survived to discharge. Cardiac activity on initial POCUS was associated with higher ROSC rates (52.1% vs. 12.3%, p < 0.001) and survival (16.7% vs. 0.69%, p < 0.001). Cardiac standstill duration ≥ 10 min had 100% specificity and positive predictive value for non-ROSC. No patients with standstill ≥ 10 min achieved ROSC or survival. Conclusion Serial POCUS during CPR can effectively predict futile resuscitation, particularly when cardiac standstill persists ≥ 10 min. The absence of cardiac activity on initial POCUS and prolonged standstill were strongly associated with non-ROSC and mortality. These findings support integrating POCUS into resuscitation protocols to guide termination decisions, though larger studies are needed for validation.